Exact Solution to the Schrodinger Equation with Manning-Rosen Potential Via Wkb Approximation Method (Global Journal of Science Frontier Research, 2018)
In quantum mechanics, exact solutions to equations play an important role because they contain a wealth of important information regarding the system under consideration. Here, we present the use of Wentzel-Kramers-Brillouin (WKB) approach toobtain the exact energy spectrum for Manning-Rosen potential and also, eigen energy solutions of special potential considered were also obtained.
Keywords: schrodinger equation; manning-rosen potential; WKB approximation